Chapter Raman Fiber Laser-Based Amplification in Telecommunications - Tan, Mingming (InTechOpen, 2018)
The chapter demonstrates a detailed study of Raman fiber laser (RFL)-based amplification techniques and their applications in long-haul/unrepeatered coherent transmission systems. RFL-based amplification techniques are investigated from signal/noise power distributions, relative intensity noise (RIN), and fiber laser mode structures. RFL-based amplification techniques can be divided into two categories according to the fiber laser generation mechanism: cavity Raman fiber laser with two fiber Bragg gratings (FBGs) and random distributed feedback (DFB) Raman fiber laser using one FBG. In addition, in cavity fiber laser-based amplification, reducing the reflectivity near the input helps mitigate the signal RIN, thanks to the reduced efficiency of the Stokes shift from the second-order pump. To evaluate the transmission performance, different RFL-based amplifiers were optimized in long-haul coherent transmission systems. Cavity fiber laser-based amplifier introduces >4.15 dB Q factor penalty, because the signal RIN is transferred from the second-order pump. However, random DFB fiber laser-based amplifier prevents the RIN transfer and therefore enables bidirectional second-order pumping, which gives the longest transmission distance up to 7915 km. In addition, using random DFB laser-based amplification achieves the distance of >350 km single mode fiber in unrepeatered DP-QPSK transmission.